Endoscope-Assisted Pectoralis Major-Rectus Abdominis Bipedicle Muscle Flap for the Treatment of Poststernotomy Mediastinitis. (March 2016) - Chou, Chieh; Tasi, Ming-jer; Sheen, Yen-Ting; Huang, Shu-Hung; Hsieh, Tung-Ying; Chang, Chih-Hau; Lai, Chung-Sheng; Chang, Kao-Ping; Lin, Sin-Daw; Lee, Su-Shin
Abstract : Introduction: Various management strategies have been reported for sternal wound care; however, they exhibit limited effectiveness or are associated with severe complications. Furthermore, it is difficult for the standard pectoralis major (PM) muscle advance flap to reach the lower third of the sternum. This article examines using the PM-rectus abdominis (RA) bipedicle muscle flap to treat lower-third deep sternal wound infection. Methods: The outcomes of patients who received a PM-RA bipedicle muscle flap harvest at our institution between 1996 and 2014 were reviewed. The method involves performing a subfascial and subperiosteal dissection of the PM to elevate the muscle flap. Blunt dissection may be performed carefully under an endoscope. Endoscope visualization enables us to identify the critical structures lateral to the PM muscle. In addition, the connective tissue to the RA muscle was preserved. Continuity was carefully preserved from the pectoral-thoracoepigastric fascia to the anterior rectus sheath. The flap could then be transposed to fill the lower-third sternal tissue defect with ease. Results: A total of 12 patients, with a mean age of 71 years (45–89 years), were treated using an endoscope-assisted PM-RA bipedicle muscle flap harvest. Wound microbiology of the 12 patients revealed that 3 patients had methicillin-resistant Staphylococcus aureus, 4 had S. aureus, 1 had coagulase-negative Staphylococcus, 1 had Escherichia coli, 1 had Pseudomonas aeruginosa, 1 had Mycobacterium tuberculosis, and 1 had a mixed growth of organisms. One instance of recurrent sternal infection was identified among the patients. Moreover, 1 patient died from heart failure 5 weeks after surgery, but the coverage of the sternal wound was successful. Accidental injury to the surrounding neurovascular structure of the patients was avoided, and only 10 to 15 minutes was required to divide the PM muscle. Conclusions: Performing this harvest method under endoscopic assistance has several advantages, such as preventing excess traction of the skin edge to diminish the skin slough. This method could be an effective alternative for harvesting the PM-RA bipedicle muscle flap to reconstruct the lower-third sternal wound.